A new lacewing (Insecta: Neuroptera: Grammolingiidae) from the Middle Jurassic of Inner Mongolia, China - Liu, Yushuang; Shi, Chaofan; Ren, Dong (Zootaxa, 2011)
A new species of the family Grammolingiidae (Neuroptera) (Leptolingia imminuta sp. nov.) is described from Daohugou village (Middle Jurassic), Inner Mongolia, China. In this new species, MA forks at the same level as the separation of Rs2 from Rs, close to the middle of forewing, this structure of MA is peculiar in Grammolingiidae and is different from that of all other known species. Moreover, this new species is the smallest species known in the family Grammolingiidae (30 mm wing span).